Labeling of nascent RNA in the C. elegans intestine - Omid Gholamalamdari; Stephanie C. Weber (PLoS ONE, 2026)
Transcriptional regulation in C. elegans has been difficult to study at the level of nascent RNA because nucleotide analogs do not readily penetrate the cuticle. Here, we establish an ex vivo 5-ethynyl uridine (EU)-click labeling protocol that enables sensitive microscopy detection of newly transcribed RNA in dissected intestines. Using worms expressing fluorescent nucleolar markers, we show that EU incorporation faithfully reports on nascent transcription in both the nucleoplasm (mRNA) and the nucleolus (rRNA) and is abolished by inhibition of RNA polymerases. Spatial analysis further reveals that the majority of nascent rRNA transcripts localize to the fibrillar zone (FZ) of intestinal nucleoli, consistent with the conserved role of this compartment in rRNA synthesis. In addition to imaging applications, this workflow can be adapted for gene expression assays, providing a versatile approach for quantitative analysis of nascent transcription in C. elegans . By enabling direct visualization of nucleolar transcription in intact intestine tissue, this method opens new opportunities to investigate how nucleolar activity is regulated across development, aging, and disease contexts.